2014
DOI: 10.2527/jas.2014-8124
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impacts of genetically engineered feedstuffs on livestock populations1

Abstract: Globally, food-producing animals consume 70 to 90% of genetically engineered (GE) crop biomass. This review briefly summarizes the scientific literature on performance and health of animals consuming feed containing GE ingredients and composition of products derived from them. It also discusses the field experience of feeding GE feed sources to commercial livestock populations and summarizes the suppliers of GE and non-GE animal feed in global trade. Numerous experimental studies have consistently revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(76 citation statements)
references
References 92 publications
1
72
0
1
Order By: Relevance
“…These claims include the link between GMOs and organ damage; GMOs leaving traces of modified genetic material in human bodies; and the potential for GMOs to mix with unrelated species, thereby creating new toxins, allergens, and carcinogens. However, other scientific investigations have concluded that such claims are unfounded (Netherwood et al 2004, Paarlberg 2009, Bennett et al 2013, Van Eenennaam & Young 2014. Despite such scientific studies, it is likely that, as Greene (2013Greene ( , 2014 argues, the demand for natural produce will continue to flourish.…”
mentioning
confidence: 96%
“…These claims include the link between GMOs and organ damage; GMOs leaving traces of modified genetic material in human bodies; and the potential for GMOs to mix with unrelated species, thereby creating new toxins, allergens, and carcinogens. However, other scientific investigations have concluded that such claims are unfounded (Netherwood et al 2004, Paarlberg 2009, Bennett et al 2013, Van Eenennaam & Young 2014. Despite such scientific studies, it is likely that, as Greene (2013Greene ( , 2014 argues, the demand for natural produce will continue to flourish.…”
mentioning
confidence: 96%
“…However, the adoption of GM in forage grasses and legumes lags behind that in crops, and is limited to herbicide-resistant lucerne (Medicago sativa) (James 2013) and, more recently, a low-lignin trait in lucerne. However, there is substantial interest in output traits for animal production (Van Eenennaam and Young 2014).…”
Section: Gene Technologymentioning
confidence: 99%
“…While there is no scientific evidence supporting any claims of detrimental side effects of GMOs in the modification of approved food [10,11], social media is dominated by claims of disastrous effects on animals and human consumers. Not only is a large portion of the animal feed in the US already genetically modified [12] without any obvious effect, GMOs need to play a critical role in addressing the enormous and expanding malnutrition in many developing countries specifically in Africa or India [13]. The development and utilization of vaccines have prevented devastating epidemics decimating whole communities and regions in the past.…”
Section: The Concept Of Resiliencementioning
confidence: 99%